Análise numérica do desempenho de um motor diesel turboalimentado operando com mistura óleo diesel-biodiesel de mamona - Rocha, Danilo Sousa (2011)
The effects of the addition of biodiesel to mineral diesel oil were studied employing dynamometer tests and multidimensional simulations. The impact of this addition upon the dynamics of the fuel jet and upon the formation of nitrogen oxides was accessed employing the multidimensional code KIVA 3 VR2 to carry out the computational simulations, which were validated against experimental curves of in cylinder pressure. The utilized fuels were diesel oil and B20 blend, comprising of 80% diesel oil and 20% methyl ester of castor oil, by volume. The results indicate that the addition of biodiesel causes an increase in the penetration of the fuel jet due to its lower atomization characteristics compared to diesel oil. Emissions of nitrogen oxides were higher with the use of B20 blends, due to an increase in the share of fuel jet exposed to high temperatures and lean burning conditions compared to stoichiometric.